Biological Applications of The Newly Designed Phthalocyanine‐Modified Gold Nanorods - Öztürk, Nazlı Farajzadeh; Özdemir, Sadin; Giray, Gülay; Aftab, Javaria; Bayır, Zehra Altuntaş (Wiley, 2024)
Abstract In this study, a new di‐substituted phthalonitrile derivative namely 2‐[2‐{(3,5‐bis (trifluoromethyl) phenyl) ethynyl}‐4,5 dicyanophenyl] malonate was synthesized. The cycloteramerization of the resultant compound in the presence of the related metal salts resulted in a number of metal {M=Co, Mn, and Lu} phthalocyanines. The newly synthesized macromolecules were used for the functionalization of gold nanorods. To study the effect of modification and metal ion on the biological properties of the gold nanorods, the biological features of the phthalocyanines, phthalocyanine‐gold nanorod conjugates, and gold nanorods were examined by performing different biological approaches. In this study, the anti‐diabetic activities of fluorinated phthalocyanines and their gold nanorod conjugates were examined for the first time using pancreatic alpha‐amylase. The antioxidant activities of the studied nano/structures were analyzed using 2,2‐diphenyl‐1‐picrylhydrazil (DPPH) radical scavenging assay. Their antimicrobial and antimicrobial photodynamic therapy activities (APDT) were investigated, as well. They exhibited good DNA cleavage activities. The highest biofilm inhibition activities were obtained 97.49 and 91.53 % for 200 mg/L of nanoconjugate ( 7 ) against S. aureus and P. aeruginosa , respectively. All the studied biological candidates also displayed effective microbial cell viability inhibition activities against E. coli .